Ecological distribution and population structure of Acantholobulus schmitti (Rathbun, 1930) (Crustacea, Decapoda, Xanthoidea) on the southeastern Brazilian coast - Fransozo, Vivian; Silva, Thiago Elias Da [UNESP]; Fumis, Patrícia Bianca [UNESP]; Bertini, Giovana [UNESP]; Lima, Paloma Aparecida De [UNESP] (Universidade de São Paulo (USP), Instituto Oceanográfico, 2013)
This investigation analyzed the ecological distribution and population structure of A. schmitti on the southeastern coast of Brazil. Crabs were sampled monthly from January 1998 to December 1999 at the following bays: Ubatumirim (UBM), Ubatuba (UBA) and Mar Virado (MV). Water and sediment samples were also collected from all sampling sites for an analysis of environmental factors. Acantholobus schmitti was most abundant at UBM (224), followed by UBA (154) and MV (23) but its abundance showed no association with the environmental factors analyzed. The low abundance of these crabs in MV may be due to the high wave action that moved biodetritic material accumulated on the bottom and frequently removed small crabs from their sheltered positions among the shell fragments. The individuals captured included 269 males and 132 females, of which only 4 specimens were brooding females. Juvenile recruitment occurred throughout the year, but was less intense in the spring. The major abundance of individuals as well as of ovigerous females occurred during 1999, when the entrance of the South Atlantic Central Waters (SACW) was stronger than in previous year. This environmental influence could be the main factor modulating this population.

Os objetivos deste estudo foram analisar a distribuição ecológica e a estrutura populacional de A. schmitti no litoral sudeste brasileiro. Os caranguejos foram coletados, mensalmente, de janeiro de 1998 a dezembro de 1999 nas enseadas: Ubatumirim (UBM), Ubatuba (UBA) e Mar Virado (MV), onde também foram obtidas amostras de água e sedimento para análise dos fatores ambientais. A maior abundância de A. schmitti foi verificada em UBM (224), seguida por UBA (154) e MV (23) e não apresentou associação com os fatores ambientais analisados. O motivo da baixa abundância desses caranguejos em MV pode ser a alta ação de ondas que movimenta o material biodetrítico acumulado no fundo e, frequentemente, remove pequenos caranguejos de seus abrigos entre fragmentos de conchas. Os indivíduos foram 269 machos e 132 fêmeas, das quais apenas 4 eram ovígeras. O recrutamento juvenil ocorreu o ano todo, sendo menos intenso na primavera. A maior abundância de indivíduos, bem como as fêmeas ovígeras, ocorreu em 1999, quando a entrada da Água Central do Atlântico Sul (ACAS) foi mais intensa do que no ano anterior. Esta influência ambiental pode ser o principal fator modulador para esta população.
Keywords: Fatores ambientais; Panopeidae; Abundância; Massas de água; Environmental factors; Panopeidae; Abundance; Water mass